All-Optical Switching Based on the Plasma Channel Induced by Laser Pulses - Chao Tan; Binliang Hu; Shiping Zhan; Yonghua Hu; Bin Zhong (Advances in Condensed Matter Physics)
We display a theoretical and experimental study of all-optical switching for signal lasers based on the plasma channel induced by the control laser. Using the plasma channel generated in the carbon disulfide (CS2) solution, the signal light can be modulated as some spatial distributions including unchanging, ring-shaped beam, and other intensity profiles. The modulation on the signal light can be conveniently adjusted by changing the control light’s incident intensity distribution. We can infer the dark spot shape in the modulated signal laser through the intensity profile of control laser beam. These results provide the great potential of plasma channel induced by lasers as an all-optical switching for various optoelectronic applications.